Maximal oxygen consumption requirements in professional north american ice hockey - Ferland, P. M.; Marcotte-L'Heureux, V.; Roy, P.; Carey, V. D.; Charron, J.; Lagrange, S.; Leone, M.; Comtois, A. S. (The Journal of Strength and Conditioning Research, 2021)
This study was designed to measure preseason on-ice relative Vo2max of professional ice-hockey players (n = 101 National Hockey League [NHL], 42 American Hockey League [AHL], 4 East Coast Hockey League [ECHL], and 15 Canadian Hockey League [CHL]) throughout 17 years and compare it between generations, league level, and position, and to verify if it was related to season and NHL career statistics. Relative Vo2max was measured on ice with a portable metabolic analyzer (K4b2, Cosmed, Rome) with full hockey equipment, except for the helmet with either the Skating Multistage Aerobic Test or the 30-15 intermittent ice test tests. Relative Vo2max results from both tests were compared between players of the same generation with an independent-samples T-test and were not significantly different. A one-way analysis of variance and post hoc pairwise tests were performed to detect significant differences between groups. Pearson correlations (two-tailed) were also performed between selected variables. All statistical significance was set at p < 0.05. Results show that there are no significant differences for relative Vo2max between generations (2001-2003 vs. 2006 vs. 2015-2017), league level (NHL vs. AHL vs. ECHL vs. CHL), and position (winger, center, and defense), other than the ECHL being lower. There are also no significant relationships between VO2max values and hockey season and NHL career statistics. Thus, the results show that there is a minimal relative Vo2max requirement to play North American ice hockey at the elite level (55.9 ± 5.2 ml/kg/min; n = 162). Future research should be directed toward comparing VO2max of elite and amateur ice-hockey players to confirm the minimal relative VO2max requirement to play North American ice hockey at the elite level.